Di-ureasil hybrid electrolytes incorporating a new proton ionic liquid - Cardoso, Marita A. (2016)
The protic ionic liquid (PIL) N-butylimidazolium trifluoromethanesulfonate ([BIm][TfO]) was obtained for the first time and incorporated into a sol-gel derived di-ureasil matrix with a concentration of X = 5, 10 and 30 %, where X is the ratio of the mass of PIL per mass of poly(oxyethylene) (POE). Four years after their synthesis, the resulting quasi-anhydrous electrolytes remained amorphous, homogeneous, flexible and thermally stable below 200 ºC. SEM/EDS data revealed the presence of the PIL at the surface of the xerogels with X > 5 %, demonstrating that this type of morphological characterization is mandatory to avoid misleading ionic conductivity values. The highest ionic conductivity was produced in the washed sample with X = 30 % (3.5 x10-5 and 2.1x10-3 S cm-1 at 25 and 170 ºC, respectively). The present family of electrolytes yielded higher conductivities than the N-ethylimidazolium trifluoromethanesulfonate-based analogues introduced earlier by our group and may be thus considered as promising candidates for applications in fuel cells.